(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2022)
The aim of the article was to analyze the phenomenon of underemployment in terms of gender equality in the labor market in Poland between 2005-2019. The article investigates whether the same tendencies of changes occure amongst underempolyed men and women. In addition, the part-time employment was outlined together with the employed and unemployed in Poland within the above-mentioned years in order to examine the research problem more extensively. The author of the article used simple statistical tools, such as: analysis of the dynamics of changes in the form of a measure of relative increase with a variable base and the average rates of changes of the phenomenon over time. The conducted research allowed to determine the average values in individual years and indicate the periods with the highest and the lowest results. Moreover, the applied tools made it possible to determine the annual changes among the underemployed, employed and unemployed. The article uses data gained from the International Labor Organization together with literature related to the topic of the examination including foreign literature.